2014
DOI: 10.1111/echo.12693
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Strain and Strain Rate Imaging of the Left Atrium and Left Ventricle in Adult Patients with Atrial Septal Defects before and after the Later Stage of Percutaneous Device Closure

Abstract: LA and LV S and SR are not significantly affected in ASD patients. However, correction of the long-standing volume overload by percutaneous closure causes an early increase in LA and LV longitudinal deformation that correlates with the magnitude of the atrial septal defect. But this increase decreased in 1 month after closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…The continuation of the remodeling effect of previous ASD shunting may be another possible explanation . Furthermore, we found that an impaired LA reservoir and conduit function and an impaired RA contraction function were more probable in our patients who underwent device ASD closure, which is concordant with some previous research . The presence of a device anchoring on an atrial wall without deformation of any magnitude may lead to decreased longitudinal deformation in the other walls.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The continuation of the remodeling effect of previous ASD shunting may be another possible explanation . Furthermore, we found that an impaired LA reservoir and conduit function and an impaired RA contraction function were more probable in our patients who underwent device ASD closure, which is concordant with some previous research . The presence of a device anchoring on an atrial wall without deformation of any magnitude may lead to decreased longitudinal deformation in the other walls.…”
Section: Discussionsupporting
confidence: 90%
“…Cakal et al compared the LA functions as assessed with 2D speckle‐tracking echocardiography between 20 adult patients with ASD who were candidates for device ASD closure and 20 healthy participants. They reported that before closure, the LA functions were not different between their groups; nonetheless, 24 hours after closure, all of the LA functions were increased, and at 1 month, the peak systolic strain (the index of the reservoir function) was increased, whereas the peak systolic strain rate, early diastolic strain rate, and late diastolic strain (the indices of the reservoir, conduit, and contraction functions of the LA, respectively) were reduced compared with the preclosure values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations